Plant leaves as templates for soft lithography. Issue 27 (25th February 2016) - Wu, Wenming; Guijt, Rosanne M.; Silina, Yuliya E.; Koch, Marcus; Manz, Andreas
Abstract : Complex microvascular venation patterns of natural leaves are replicated into PDMS replicas, which allows for a leakage-tight seal with a flat substrate despite the surface topography. Abstract : We report a simple fast, practical and effective method for the replication of the complex venation patterns of natural leaves into PDMS with accuracy down to a lateral size of 500 nm. Optimising the amount of crosslinker enabled the replication and sealing of the microvascular structures to yield enclosed microfluidic networks. The use of plant leaves as templates for soft lithography was demonstrated across over ten species and included reticulate, arcuate, pinnate, parallel and palmate venation patterns. SEM imaging revealed replication of the plants microscopic and sub-microscopic topography into the PDMS structures, making this method especially attractive for mimicking biological structures for in vitro assays. Flow analysis revealed that the autonomous liquid transport velocity in 1 st -order microchannel was 1.5–2.2 times faster than that in the 2 nd -order microchannels across three leaf types, with the sorptivity rule surprisingly preserved during self-powered flow through leaf-inspired vascularity from Carpinus betulus .